Antimicrobial Resistance in Pasteurellaceae Isolates from Pyrenean Chamois (Rupicapra pyrenaica) and Domestic Sheep in an Alpine Ecosystem - Irene Torres-Blas; Xavier Fernández Aguilar; Oscar Cabezón; Virginia Aragon; Lourdes Migura-García (Animals, 2021)
Antimicrobial resistance (AMR) has spread worldwide due to the inappropriate use of antimicrobial drugs in human and veterinary medicine, becoming a public health problem. However, little is known about its occurrence and maintenance in wild animals, and very few studies have been carried out in ecosystems subjected to low human pressure. In our study, nasal and lung swabs were collected from hunted Pyrenean chamois (Rupicapra pyrenaica), and nasal swabs from sympatric domestic sheep were also collected. The swabs were cultured in agar plates to obtain bacterial isolates from the Pasteurellaceae family. The presence of AMR was assessed in a total of 28 Pasteurellaceae isolates from 45 Pyrenean chamois, and 9 isolates from sympatric domestic sheep found in the National Hunting Reserve of Freser-Setcases (Northeastern Pyrenees, Spain). The isolates belonged to one of the following three species: Pasteurella multocida, Mannheimia haemolytica and Bibersteinia trehalosi. Some P. multocida and M. haemolytica isolates tested positive for AMR. The statistical analysis revealed no differences between the AMR levels from chamois and domestic sheep isolates. However, one P. multocida of chamois origin presented resistance to cephalosporins and fluoroquinolones, which are antibiotics of critical importance for human health. Further studies are required to elucidate potential routes of dissemination of AMR genes in natural environments and assess any significant persistence in wildlife to design risk mitigation actions.